The second century of cinema : the past and future of the moving image - Dixon, Wheeler W., 1950- (State University of New York Press, 2000)
The author "explores the possible effects of the digital age on the production and exhibition of films."--Cover
Keywords: Motion pictures.; Motion Pictures; Cinéma.; PERFORMING ARTS -- Film & Video -- Reference.; Motion pictures; Filmkunst.; Filmindustrie.; Toekomstverwachtingen.; Filosofische aspecten.; Film.; Music, Dance, Drama & Film.; Films.